PERAN DANA INFAK DAN SEDEKAH DALAM MENINGKATKAN KESEJAHTERAAN SOSIAL DALAM PERSPEKTIF EKONOMI MAKRO ISLAM - Uktafi Karunia; Maya Ari Sofiana; Khasna Maulida; Muhammad Taufiq Abadi (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
The aim of this research is to determine the role of infaq and alms funds in improving social welfare from an Islamic macro perspective. This research uses a qualitative method with a qualitative descriptive approach. The main technique in this research is to collect data using a literature review technique which is a technique for collecting several articles which will be used as a reference by the author in preparing the article. The results obtained from this research are that infaq and alms activities have a religious purpose in overcoming social problems. Infaq and alms funds not only play a role in social life, but also support economic growth and strengthen social, economic and spiritual aspects in society in accordance with Islamic principles.